EVALUASI PENERAPAN BLENDED LEARNING PADA PEMBELAJARAN BAHASA ARAB DI SMPIT IBADURRAHMAN: STUDI KASUS DI KELAS VII AKHWAT - Khaerunnisa, Fahtu (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2019)
The purpose of this study is to provide an overview about the application of blended learning especially during the distance education. This study used a qualitative approach with case study methods. Data collection conducted through interviews, observations and documentation studies. Based on the results of the study, in the learning planning activities, teacher prepared lesson plan, syllabus, face-to-face scheduling, teaching materials and evaluation tools that form as soft files. The learning process is carried out in three stages: the initial, core and final activities. Evaluation of learning in the form of assignments, midterm and final examination. When the implementation of blended learning used there are several obstacles that teachers feel